1994
DOI: 10.1007/bf00202867
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of the human histamine H1-receptor gene

Abstract: We have assigned the human histamine H1-receptor gene to chromosome 3 by Southern blot analysis of a chromosome mapping panel constructed from human-hamster somatic cell hybrids. This assignment was confirmed by in situ hybridization on metaphase chromosomes and involved bands 3p14-p21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…This led rapidly to the cloning of the receptor cDNA in several species, including human in 1993(De Backer et al, 1993Moguilevsky et al, 1994). The human gene was subsequently localized to chromosome 3p14-p21 (Le Coniat et al, 1994). A single H 1 receptor polymorphism rs7651620 Glu270Gly has been identified that is relevant to African subjects only (Garcia-Martin et al, 2009;Micallef et al, 2013).…”
Section: A Receptor Structurementioning
confidence: 99%
“…This led rapidly to the cloning of the receptor cDNA in several species, including human in 1993(De Backer et al, 1993Moguilevsky et al, 1994). The human gene was subsequently localized to chromosome 3p14-p21 (Le Coniat et al, 1994). A single H 1 receptor polymorphism rs7651620 Glu270Gly has been identified that is relevant to African subjects only (Garcia-Martin et al, 2009;Micallef et al, 2013).…”
Section: A Receptor Structurementioning
confidence: 99%
“…All of these receptors belong to the G protein-coupled receptor family. They are heptahelical transmembrane molecules that transduce extracellular signals by using G proteins and intracellular second messenger systems [10, 13]. The active and inactive states of HRs exist in equilibrium.…”
Section: Histamine Receptorsmentioning
confidence: 99%
“…There are four major types of histamine receptors: H1, H2, H3 and H4 receptors which differ in their expression, signal transduction and function (38)(39)(40)(41)(42)(43)(44)(45). Exspression of H1 and H2 receptors are widely expressed in contrast to H2 and H4 receptors.…”
Section: Hi St a M I Ne Re Ce P T Orsmentioning
confidence: 99%